Analysis of New Media Communication Effect of Sports Advertisement Based on Audience Psychological Effect - Ming Xu; Chunjing Bai; Sheng Wei (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In modern times, sports advertising has become a new challenge that cannot be met through the traditional media communication network. This challenge in communication and advertising has contributed to current difficulties in effective communication. This study investigates the mechanism and effect of new media advertisement communication, assists advertisers and producers in serving advertisements on new media platforms more efficiently, and enhances the communication effect of product/service advertisements. This study examines the methods for obtaining sports advertising from new media platforms, and the interaction style of sports advertising in the new media communication network (NMCN). Based on the frequency and similarity of information propagation, an NMCN communication model was built. A comprehensive evaluation technique was used to examine the impact of new media communication on sports advertising. The simulated mean capacity of our network nodes to transmit advertisement data corresponds to their actual capacity. At all prevalence levels, the simulated infection density of network nodes corresponds to that predicted by our model. The transmission scale of sports advertisements in the network continued to expand as the transmission rate increased; the transmission threshold lowered as the effect coefficient increased. The number of views was limited, and the click-through rate improved when the advertisement was shown on the new media. Based on the frequency and similarity of information transmission, an innovative communication model was developed for the new media communication network (NMCN). The optimal service of sports advertising on new media can enhance the audience's attention, cognition, interaction, and behavior. This research has theoretical and practical implications for sports advertising media communication literature and practice.